Odpowiedzi

Najlepsza Odpowiedź!
2010-03-08T16:31:32+01:00
Oblicz :
a) 6+(-4)+(-10)=6-4-10=-8
-4-(-9)-3=-4+9-3=2
-16+7-28=-37
b) 4,3-7,4+1,1=-2
(-6,2)+1,6-(-2,3)=(-6,2)+1,6+2,3=-2,3
7,8-5,4-12,1=-9,7
c) minus jedna cała 1/3-2/9+1/6=(-25/18)=(-1 i 5/18)
jedna cała 1/8-dwie całe 1/4 - (-1/2)=(-23/8)=(-2 i 7/8)
(-2,1)+1/5 -3=(-4,9)
2010-03-08T16:36:58+01:00
6+(-4)+(-10) = -8
-4-(-9)-3 = 2
-16+7-28 = - 37
b) 4,3-7,4+1,1 = -2
(-6,2)+1,6-(-2,3) = -2,3
7,8-5,4-12,1 = -9,7
c) minus jedna cała 1/3-2/9+1/6 = - 25/18
jedna cała 1/8-dwie całe 1/4 - (-1/2) = - 6/8 = - 3/4
(-2,1)+1/5 -3 = - 7/10
1 5 1